An assessment of the frequency of book loss between open and closed stack systems in selected University of the Philippines libraries a follow-up study - Acuña, Patrice Yvannah B.
Book loss has always been a problem libraries face. Geared by the latest technology for libraries, book loss can be minimized if not completely eradicated. Given the recommendations to minimize book loss indicated in a study conducted 14 years ago on the prevalence of book loss on both stack systems and the changes in security, policies, and practices carried out by the libraries, the study aims to find out whether these recommendations were implemented by the libraries utilized in the previous study and if there were any effects on the number of losses in both stack systems.